Multifunctional Photonic Nanomaterials for Diagnostic, Therapeutic, and Theranostic Applications. Issue 10 (24th January 2018) - Kim, Hyemin; Beack, Songeun; Han, Seulgi; Shin, Myeonghwan; Lee, Taehyung; Park, Yoonsang; Kim, Ki Su; Yetisen, Ali K.; Yun, Seok Hyun; Kwon, Woosung; Hahn, Sei Kwang
Abstract: The last decade has seen dramatic progress in the principle, design, and fabrication of photonic nanomaterials with various optical properties and functionalities. Light‐emitting and light‐responsive nanomaterials, such as semiconductor quantum dots, plasmonic metal nanoparticles, organic carbon, and polymeric nanomaterials, offer promising approaches to low‐cost and effective diagnostic, therapeutic, and theranostic applications. Reasonable endeavors have begun to translate some of the promising photonic nanomaterials to the clinic. Here, current research on the state‐of‐the‐art and emerging photonic nanomaterials for diverse biomedical applications is reviewed, and the remaining challenges and future perspectives are discussed. Abstract : Photonic nanomaterials are extensively investigated for various biomedical applications with the advantages of their small size, unique optical properties, and multiple functionalities. An in‐depth overview of the current state‐of‐the‐art research on multifunctional photonic nanomaterials is provided to elucidate their potential in diagnostic, therapeutic, and theranostic applications with perspectives on the foreseeable challenges toward a new era of futuristic nanomedicines.